Antitumor effect of WEE1 blockade as monotherapy or in combination with cisplatin in urothelial cancer. Issue 9 (29th July 2021) - Murakami, Kaoru; Kita, Yuki; Sakatani, Toru; Hamada, Akihiro; Mizuno, Kei; Nakamura, Kenji; Takada, Hideaki; Matsumoto, Keiyu; Sano, Takeshi; Goto, Takayuki; Akamatsu, Shusuke; Saito, Ryoichi; et al.
Abstract: Overcoming cisplatin (CDDP) resistance is a major issue in urothelial cancer (UC), in which CDDP‐based chemotherapy is the first‐line treatment. WEE1, a G2 /M checkpoint kinase, confers chemoresistance in response to genotoxic agents. However, the efficacy of WEE1 blockade in UC has not been reported. MK‐1775, a WEE1 inhibitor also known as AZD‐1775, blocked proliferation of UC cell lines in a dose‐dependent manner irrespective of TP53 status. MK‐1775 synergized with CDDP to block proliferation, inducing apoptosis and mitotic catastrophe in TP53 ‐mutant UC cells but not in TP53 ‐WT cells. Knocking down TP53 in TP53 ‐WT cells induced synergism of MK‐1775 and CDDP. In UMUC3 cell xenografts and two patient‐derived xenograft lines with MDM2 overexpression, in which the p53/cell cycle pathway was inactivated, AZD‐1775 combined with CDDP suppressed tumor growth inducing both M‐phase entry and apoptosis, whereas AZD‐1775 alone was as effective as the combination in RT4 cell xenografts. Drug susceptibility assay using an ex vivo cancer tissue‐originated spheroid system showed correlations with the in vivo efficacy of AZD‐1775 alone or combined with CDDP. We determined the feasibility of the drug susceptibility assay using spheroids established from UC surgical specimens obtained by transurethral resection. In conclusion, WEE1 is a promising therapeutic target in the treatment of UC, and a highly specific small molecule inhibitor is currently in early phase clinical trials for cancer. Differential antitumor efficacy of WEE1 blockade alone or combined with CDDP could exist according to p53/cell cycle pathway activity, which might be predictable using an ex vivo 3D primary culture system. Abstract : WEE1 inhibitor and cisplatin (CDDP) in combination was significantly more effective than the single treatments. Drug susceptibility assay using an ex vivo cancer tissue‐originated spheroid system showed correlations with the in vivo efficacy of AZD‐1775 alone or combined with CDDP.